2001
DOI: 10.1007/s15010-001-1055-4
|View full text |Cite
|
Sign up to set email alerts
|

Infections Caused by Stenotrophomonas maltophilia - A Prospective Study

Abstract: S. maltophilia is not only a nosocomial pathogen. Pretreatment with a carbapenem is no longer an unequivocal risk factor for an infection with S. maltophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…12,16,52 However, recent reports based on the in vitro activity indicate newer fluoroquinolones such as trovafloxacin, clinafloxacin and moxifloxacin might have a potential role in the treatment of S. maltophilia infections. 30,36,46 In another study a considerable time -kill effect of moxifloxacin on genetically distinct isolates of S. maltophilia resistant to TMP/SMX has been demonstrated. 52 Despite that, it is important to mention ciprofloxacin-resistant mutants of S. maltophilia can be easily selected in vitro, which might have an important implication for the limited role of these agents as emipirical monotherapy.…”
Section: Treatment Of S Maltophilia Infectionmentioning
confidence: 95%
See 1 more Smart Citation
“…12,16,52 However, recent reports based on the in vitro activity indicate newer fluoroquinolones such as trovafloxacin, clinafloxacin and moxifloxacin might have a potential role in the treatment of S. maltophilia infections. 30,36,46 In another study a considerable time -kill effect of moxifloxacin on genetically distinct isolates of S. maltophilia resistant to TMP/SMX has been demonstrated. 52 Despite that, it is important to mention ciprofloxacin-resistant mutants of S. maltophilia can be easily selected in vitro, which might have an important implication for the limited role of these agents as emipirical monotherapy.…”
Section: Treatment Of S Maltophilia Infectionmentioning
confidence: 95%
“…Ceftazidime is another beta-lactam shown to have reasonable activity in some studies, usually not more than 50% of isolates are susceptible to this agent. 27,30 It can not be recommended for use as empirical therapy. Minocycline, doxycycline and chloramphenicol exhibit good in vitro activity against S. maltophilia, although the clinical experience with these agents is extremely limited.…”
Section: Treatment Of S Maltophilia Infectionmentioning
confidence: 99%
“…The respiratory tract represents the most common site of isolation of this microorganism in hospitalised patients, accounting for the origin of 56-69% of isolates; nevertheless, a positive respiratory tract culture in the majority of severely impaired hosts represents colonisation rather than invasive infection [95,97,98]. Therefore, rigorous diagnostic criteria are necessary to differentiate between colonised and infected patients [99,100].…”
Section: Stenotrophomonas Maltophiliamentioning
confidence: 99%
“…3,4 Infection with this pathogen commonly manifests as bacteremia, [1][2][3][4][5][6][7][8][9][10] although it can cause a wide spectrum of other infections as well. [11][12][13][14][15][16][17][18][19][20][21] Several studies have identified major risk factors for the infection, including neutropenia, prolonged hospitalization, previous antibiotic use, steroid use, mechanical ventilator support, and the use of medical devices such as prosthetic heart valves, urinary catheters, and indwelling central venous catheters (CVCs). [1][2][3][4][5][6][7][8][9][10]17,18 However, to our knowledge very little information is available regarding how often CVCs are the source of the bacteremia.…”
mentioning
confidence: 99%